On opinion and persuasive writing: Teaching English through editorials - Afzal, Naeem; Harun, Minah (Australian International Academic Centre, Australia, 2013)
Learning a language becomes easier when it is interpreted through certain contexts, of which, the sociocultural ones are the most important. Sociocultural interests, norms, customs and values are represented by the language as forms of “persuasive social acts”. Media discourses can be cited as one example in this regard where language is an inevitable means of communicating opinions, making one’s voice heard.Persuasive use makes media discourse interesting to explore in the classroom given the specificities in editorial writing. This paper brings forth a comparative analysis of editorial contents from two newspaper editorials published in Pakistan and Saudi Arabia. The analysis draws attention to rhetorical strategies and persuasive type of language used by the editors which can be sourced to help in the teaching and learning of English in the classroom.